Faktor Risiko Kematian Neonatal di Kabupaten Kepulauan Mentawai - Bangun, Imelda Ferawati; Abdiana, Abdiana; Edison, Edison (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2019)
Neonatal death rate for the most horrific death of an infant born alive in terms of age 0 until 28 the day. Indonesia th stage 77 the infant mortality in the world , with the death neonatal 14 per 1000 live births, while the purpose of sdgs is decreased the value of the death of neonatal until 12 per 1000 live births in years 2030. West sumatra rank the fifteenth neonatal mortality and kepulauan mentawai ranked ten. Mentawai island regency ranked ten in west. The purpose of this research is knew risk factors cause of the accident death neonatal in the island mentawai. This research use design case control .Sample case was mother with death neonatal in seribu island mentawai 2017 which consisted of 19 people .Sample control is mother with live births diwilayah island regency mentawai 2017 which consisted of 38 people .The research was done in analysis univariat and bivariat by test statistics chi-square .The results of the studies there are a significant relation exists the distance pregnancy ( p = 0,022 ), antenatal care ( p = 0,011 ), asphyxia ( p = 0,003 ), of his body weight of low birth ( p = 0,000 ) with the death of the neonatal . There was no correlation significant ( for p = 0,624 ), education ( 0,222 ), of parity ( 0,073 ), living to health facilities ( p = 0,255 ), culture ( p = 0,153 ). There was no correlation between the ages of significant, education, parity, living to health facilities, culture. There is a significant relation exists between the pregnancy, antenatal care, asphyxia, low birth weight.Angka kematian neonatal adalah kematian bayi lahir hidup dalam usia 0 sampai 28 hari. Indonesia menduduki peringkat ke 77 Angka Kematian bayi di dunia, dengan angka kematian neonatal 14 per 1000 Kelahiran Hidup, sedangkan tujuan SDGs adalah menurunkan angka kematian neonatal hingga 12 per 1000 Kelahiran Hidup pada tahun 2030. Sumatera Barat peringkat kelima belas angka kematian neonatal dan Kabupaten Kepulauan Mentawai menduduki peringkat sepuluh. Tujuan penelitian ini adalah diketahuinya faktor risiko penyebab kejadian kematian Neonatal di Wilayah Kabupaten Kepulauan Mentawai. Penelitian ini mengunakan desain case control. Sampel kasus adalah ibu dengan kematian neonatal di wilayah Kabupaten Kepulauan Mentawai tahun 2017 yang berjumlah 19 orang. Sampel kontrol adalah ibu dengan kelahiran hidup diwilayah kabupaten kepulauan Mentawai tahun 2017 yang berjumlah 38 orang. Analisis penelitian dilakukan secara univariat dan bivariat dengan uji statistik chi-square. Hasil penelitian terdapat hubungan yang signifikan jarak kehamilan (p=0,022), antenatal care (p=0,011), asfiksia (p=0,003), BBLR (p=0,000) dengan kematian neonatal. Tidak terdapat hubungan yang signifikan umur (p=0,624), pendidikan (0,222), paritas (0,073), jarak rumah ke fasilitas kesehatan (p=0,255), budaya (p=0,153). Tidak terdapat hubungan yang signifikan antara umur, pendidikan, paritas, jarak rumah ke fasilitas kesehatan, budaya. Terdapat hubungan yang signifikan antara jarak kehamilan, antenatal care, asfiksia, berat badan lahir rendah.